Amorphous TiO2 nanotube arrays with Au nanocrystals for lithium‐ion battery. (13th January 2022) - Zhang, Wanggang; Liu, Yiming; Song, Zhiyuan; Yang, Fuqian
Summary: The controllable production of TiO2 ‐based nanostructured composites has attracted great interest for the potential applications in storage energy, catalysis, and photonics. In this work, we demonstrate a facile method to produce amorphous TiO2 nanotube (a‐TNT) arrays with Au nanocrystals (Au NCs) anchoring on the outmost surfaces of the a‐TNTs (Au@TNT arrays) at room temperature. The spatial distribution of Au NCs along the longitudinal direction of the a‐TNT arrays is tunable via the control of the sputtering time of Au. The Li‐ion half cells (LIHCs) with the working electrode made from the Au@TNT arrays possess higher specific capacities than those with pure a‐TNT arrays and exhibit great rate performance. The LIHCs with the Au@TNT arrays prepared with 60 seconds of the Au sputtering time exhibit the best rate performance and deliver discharge capacities of 320, 291, 286, 135, and 122 mAh·g −1 at current densities of 0.1, 0.5, 1, 5, and 10 A·g −1, respectively. The apparent diffusivity of lithium in the LIHCs increases linearly with the increase of the average size of Au NCs (amount of Au NCs/sputtering time). The results obtained in this work suggest that a‐TNTs anchored with metallic nanocrystals have the potential to be anode materials of next‐generation lithium‐ion battery.